Status, diversity and potential of indigenous and minor perennial vegetables - Sharma, A K; Annepu, Sudheer Kumar (Indian Horticulture, 2020)
Despite possessing an immense value as a nutritious food source, many indigenous and minor perennial vegetable crops remain widely unknown. Still cultivation and their consumption are restricted to few sections of the society. Given the rapid decline on traditional knowledge on these crops, it is pertinent to document the existing diversity, assorted usage and information on cultivation practices. It is also true that many more indigenous and minor vegetable crops believed to be edible are yet to be documented and bring them into the scientific domain. These vegetables grow well in low input farming systems which is gaining popularity in the recent time. They have a definite role in alleviating hunger and micronutrient deficiencies. The rich diversity can also be explored to identify the genes conferring abiotic and biotic resistance for future breeding programmes. Modern scientific studies validated the therapeutic applications of the biologically active compounds identified in these crops. These applications created a greater scope for exploring the pharmaceuticals. Developing an inventory of indigenous and minor perennial vegetable crops, information on ethno botanical properties, evaluation of nutritional benefits can establish these vegetable crops as an alternative to achieve nutritional security and livelihood sustenance.